Economic globalization adapts to a new stage of development - صالح ربيع خلف; حسن خميس محمد (Journal of Economics and Administrative Sciences, 2012)
the pursue of social systems history present to us solid evidence that the collapse of that systems be caused by either the stagnancy aftermath maturity or unreal intellectual foundation which lead to sudden collapse, while the capitalism can avoided that intellectual damages due to its dynamic system with appropriate auto adaptation mechanism and use it excellently in the right time. The globalization had excrete (as one of the capitalism adaptation mechanism) its own targets and its methods in framework of multinationals corporations which consist with capitalism states that employed the international organizations to reconstruction the global economy to serve such targets. So the globalization can eventually to ply efficiently the command roll to achieve the adaptation within the capitalism system through many mechanisms such as the matereal, qualitative, technical, intellectual, and institutional appliances that applied by the system for adaptation achievements.